Eat, Shit, Scar. Issue 1 (2nd November 2021) - Elwell, J. Sage
Abstract : By leveraging two metaphors central to discussions around the digitization of sacred texts—"books are bodies" and "translation is feeding"—this essay contends that the translation of analog sacred texts into digital formats is a metaphorical gastrointestinal process. This essay accomplishes this through the application of actor-network theory. Central to actor-network theory is the claim that an object, like a book, is the product of a complex network of relationships that together create it and constitute its meaning. Importantly, this includes discourses about the very networks that yield the object in question. As such, this essay incorporates many of the voices that appear elsewhere in this special edition as well as assorted ephemera from my own medical history of gastrointestinal maladies. If books are bodies and translation is feeding, then problems surrounding the digitization of analog sacred texts reside somewhere between ingestion and excretion.